Mexico : Arrangement Under the Flexible Credit Line and Cancellation of Current Arrangement-Press Release; Staff Supplement; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
The government has successfully maintained external, financial, and fiscal stability despite the deepest recession in decades. However, Mexico is bearing a very heavy humanitarian, social, and economic cost from COVID-19, including over half a million excess deaths, sizable under-employment, and an increase in poverty.